Historical roots of histrionic personality disorder - Novais, Filipa; Araújo, Andreia M.; Godinho, Paula (Frontiers in Psychology, 2015)
Histrionic Personality Disorder is one of the most ambiguous diagnostic categories in psychiatry. Hysteria is a classical term that includes a wide variety of psychopathological states. Ancient Egyptians and Greeks blamed a displaced womb, for many women’s afflictions. Several researchers from the 18th and 19th centuries studied this theme, namely, Charcot who defined hysteria as a “neurosis” with an organic basis and Sigmund Freud who redeﬁned “neurosis” as a re-experience of past psychological trauma. Histerical personality disorder (HPD) made its first official appearance in the Diagnostic and Statistical Manual of Mental Disorders II (DSM-II) and since the DSM-III, histrionic personality disorder is the only disorder that kept the term derived from the old concept of hysteria. The subject of hysteria has reflected positions about health, religion and relationships between the sexes in the last 4000 years, and the discussion is likely to continue.